2012
DOI: 10.1007/s00417-011-1921-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with enlargement of chorioretinal atrophy after intravitreal bevacizumab for myopic choroidal neovascularization

Abstract: Our findings showed that eyes with a larger CNV at the baseline and longer follow-up period had a greater risk of developing a ChRA like non-treatment, even if IVB treatment was performed for mCNV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…This confirms previous reports that chorioretinal atrophy can develop long after CNV has regressed not only in nontreated eyes, but also in eyes treated with PDT and/or anti-VEGF [7,27,28]. Therefore, more studies with long-term follow-up are needed to determine the real effectiveness of different treatments for myopic CNV.…”
Section: Discussionsupporting
confidence: 87%
“…This confirms previous reports that chorioretinal atrophy can develop long after CNV has regressed not only in nontreated eyes, but also in eyes treated with PDT and/or anti-VEGF [7,27,28]. Therefore, more studies with long-term follow-up are needed to determine the real effectiveness of different treatments for myopic CNV.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, several authors reported that the initial CNV size, the number of intravitreal injections and the duration of the follow-up periods were the factors most significantly associated with an enlargement of the choroidal atrophy around a regressed myopic CNV [29,30]. There still is much debate about the influence of multiple repeated intravitreal injections of bevacizumab on the development and enlargement of choroidal atrophy in patients affected by myopic CNV [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…There still is much debate about the influence of multiple repeated intravitreal injections of bevacizumab on the development and enlargement of choroidal atrophy in patients affected by myopic CNV [28][29][30]. Uemoto et al showed that eyes with an enlargement of the CRA area had received significantly more intravitreal injections of bevacizumab than eyes whose choroidal thickness was unchanged [30]. The authors suggested that this finding may be ascribed to an increase in the tension on the RPE given by the high number of intravitreal injections of VEGF inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the development of CRA and the number of anti-VEGF injections is unclear,; in a study by Ahn et al subfoveal choroidal thickness was found to be significantly decreased following anti-VEGF therapy which may play a role in eventual development of CRA [89]. Two studies provide conflicting evidence on the effects of anti-VEGF treatments on CRA size and enlargement [87,90]. Recently with the advent of swept source OCT, what was previously reported as CRA post mCNV is now postulated to be a macular BM defect instead.…”
Section: • Unclear Benefit Of Combination Of Anti-vegf Withmentioning
confidence: 99%